Finger Painting Activities and Their Effects on Creativity in Early Childhood - Sharen Mella Bungge; Durrotunnisa Durrotunnisa; Hesti Putri Setianingsih; Shofiyanti Nur Zuama (Indonesian Journal of Early Childhood Educational Research (IJECER), 2025)
This study aims to determine the effect of finger painting activities on the creativity of children in Group B at Efrat Wayura Kindergarten. Using a quantitative descriptive approach, the research involved 15 children and employed observation, interviews, and documentation as data collection techniques. The findings indicate a clear improvement in children’s creativity after participating in finger painting activities. Initially, many children demonstrated limited creative expression; however, after the intervention, a significant shift occurred, with more children showing higher levels of creative ability, including greater originality, imagination, and confidence in using colors and shapes. These results show that finger painting serves as an effective learning activity for fostering creativity in early childhood.